2017
DOI: 10.5194/hess-21-863-2017
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the variations of evapotranspiration due to land use/cover change in a semiarid shrubland

Abstract: Abstract. Evapotranspiration (E T ) is an important process in the hydrological cycle, and vegetation change is a primary factor that affects E T . In this study, we analyzed the annual and inter-annual characteristics of E T using continuous observation data from eddy covariance (EC) measurement over 4 years (1 July 2011 to 30 June 2015) in a semiarid shrubland of Mu Us Sandy Land, China. The Normalized Difference Vegetation Index (NDVI) was demonstrated as the predominant factor that influences the seasonal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 82 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…The near‐surface turbulent interactions affecting the relationship between surface fluxes and soil water content during stage‐I evaporation (Figures and ) are of particular importance for semiarid sparsely vegetated regions where soil surface interactions are known to play a critical role [ Lu et al ., ; Sun et al ., ; Nicholson , ; Gong et al ., ]. These regions cover about 50% of the global land area [ Newman et al ., ] and markedly influence local/regional carbon and water cycling and their feedbacks to the climate system [ Scott et al ., ; Lu et al ., ; Ahlström et al ., ; Gong et al ., ]. Semiarid sparsely vegetated areas are characterized by relatively low values of η and by dry soils whose upper surfaces are episodically wetted by precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…The near‐surface turbulent interactions affecting the relationship between surface fluxes and soil water content during stage‐I evaporation (Figures and ) are of particular importance for semiarid sparsely vegetated regions where soil surface interactions are known to play a critical role [ Lu et al ., ; Sun et al ., ; Nicholson , ; Gong et al ., ]. These regions cover about 50% of the global land area [ Newman et al ., ] and markedly influence local/regional carbon and water cycling and their feedbacks to the climate system [ Scott et al ., ; Lu et al ., ; Ahlström et al ., ; Gong et al ., ]. Semiarid sparsely vegetated areas are characterized by relatively low values of η and by dry soils whose upper surfaces are episodically wetted by precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to climate factors, ET is also affected by land use/cover and LUCC [5,48]. Moreover, LUCC may have a greater impact on the hydrological cycle than climate change [49].…”
Section: Discussionmentioning
confidence: 99%
“…So, it can be distinguished that air temperatures in the mountains are comparatively colder than on tidal. Previous studies have shown that vegetation, especially forests have a substantial impact and is a significant factor in influencing evapotranspiration, although plant species will provide different evapotranspiration values (Teuling, 2018;Gong et al, 2017).…”
Section: Analysis Of Evapotranspiration In Indonesian Tropical Areamentioning
confidence: 99%
“…Land degradation also causes more runoff or surface flow than infiltration, and the increasing air temperature and surface flow will increase potential evapotranspiration (Karimi et al, 2017;Rushayati et al, 2018;Ping and Liu, 2018). In contrast, researchers also found that the deforestation process can also reduce evapotranspiration because of reduced transpiration by plants (Snyman, 2001;Feddema and Freire, 2001;Zeng and Yang, 2008;Li et al, 2013;Gong, 2017;Karimi et al, 2017;Rushayati et al, 2018;Ping and Liu, 2018). Further studies needed regarding the estimation of potential evapotranspiration at the same elevation as different vegetation and the corresponding vegetation at different altitudes.…”
Section: Analysis Of Evapotranspiration In Indonesian Tropical Areamentioning
confidence: 99%